Avian influenza: the role of the pig and public health implications - KYRIAKIS (Κ. ΣΠ. ΚΥΡΙΑΚΗΣ), C. S.; van REETH, K. (Journal of the Hellenic Veterinary Medical Society, 2017)
The huge epizootics of highly pathogenic avian influenza (subtype H5N1) in Southeastern Asia over the last two years and especially the transmission of avian influenza viruses to humans have alerted the international scientific community. Many support that the threat of a new influenza pandemic appears greater today than ever before. During the 20th century, humanity has faced three pandemics, including the "Spanish flu" of 1918-19, which claimed over 20 to 40 million lives, and two less dramatic pandemics in 1957-58 and 1968-69. Influenza A viruses are single stranded RNA viruses belonging to the family Orthomyxoviridae. Their genome expresses only 10 proteins, most important of which are the two surface glycoproteins: haemagglutinin (HA) and neuraminidase (NA). So far, 16 different types of haemagglutinin (HI to Η16) and 9 of neuraminidase (Nl to N9) have been recognized. Influenza A viruses are grouped into "subtypes", according to the HA and NA surface proteins they bear (for example Η I N I , H5N2). Natural reservoirs of influenza A viruses are the wild aquatic birds (migratory waterfowl), from which all types of HA and NA have been isolated. It is important to mention that migratory waterfowl do not show clinical signs of disease, but shed the virus through their excretions.The host range of flu viruses includes domestic poultry, and mammalian species from aquatic mammals to horses, humans and swine. Because of their segmented single stranded RNA genome, influenza viruses have a very high mutation rate (genetic drift) and the possibility to undergo reassortment. Reassortment may occur when more than one virus co-infect the same cell, exchange genes and as a result, provide a totally new influenza virus (genetic shift). At least two subtypes of influenza A viruses are currendy endemic within the human population (H1N1 and H3N2), causing every year outbreaks of disease with very low mortality, especially in elders. Unlike these endemic viruses, pandemic viruses have a much higher morbidity, affecting people of all ages. Η I N I , H3N2 and H1N2 influenza viruses are currently circulating in the European and American swine population. Some of the swine influenza virus subtypes, namely Η I N I and H3N2, are thus similar to those of humans, but there are still important antigenic differences between them. Only rarely swine influenza viruses may be transmitted or cause disease to humans. Unlike mammalian influenza viruses, influenza viruses of domestic birds are grouped in two "pathotypes": low pathogenic avian influenza (LPAI) viruses, which cause localized infections and remain mild or subclinical, and highly pathogenic avian influenza (HPAI) viruses, which cause severe general infection with mortality up to 100% (fowl plague). The majority of avian influenza viruses are low pathogenic and only some, but not all, viruses of H5 and H7 subtypes are highly pathogenic. Occasionally low pathogenic Η5 or H7 viruses from wild birds transmit to poultry. Such viruses can undergo mutations in poultry as a result of which they may acquire a highly pathogenic phenotype. Until the recent avian influenza epizootics in Asia, the predominant theory for the creation of a pandemic virus supported that the pig was likely to act as an intermediate host for transmission of influenza viruses from birds to humans. The fact that genetic reassortment between human and avian viruses has also been shown to occur in pigs in nature, had led to the hypothesis that the pandemic viruses of 1957 and 1968 may have been generated through the pig. More recent data, however, come to question these theories and hypotheses: (a) the direct transmission of the H5N1 and H7N7 avian influenza viruses from birds to humans in Southeastern Asia and The Netherlands, and (b) the presence of cellular receptors recognized preferentially by the haemagglutinin of avian influenza viruses in the human conjunctiva and ciliated respiratory epithelial cells, which support that avian influenza viruses can be transmitted in toto (without reassortment) to and between humans or that humans can be the mixing vessel themselves. Furthermore, there is no solid scientific evidence to prove that any influenza virus reassortants, that have originated in swine, have posed a risk for humans. There are three criteria (conditions) an influenza virus must fulfill in order to be characterized as a pandemic virus: (a) it must be a new virus against which humans are immunologically naive, (b) it must be able to replicate in humans causing severe disease, and (c) it must be efficiendy transmitted among humans, causing wide outbreaks. So far the H5N1 influenza virus only fulfills the first and second condition, and even though it has been sporadically infecting humans for over two years, it has not yet been able to fully adapt to it's new host. Compared to the human population that may have been exposed to the H5N1 influenza virus in Asia, the number of patients and fatalities due to the H5N1 virus is very small. So far, it appears that swine do not play an important role in the epidemiology of this specific virus. Experimental infections of swine with highly pathogenic H5N1 virus have shown that it does not replicate extensively in pigs. Additionally, extensive serological investigations in the swine population of Viet Nam, indicated that the H5N1 virus merely spread to a very small number (~0.25%) of contact animals within the epizootic regions. Nevertheless, it is critical to continue monitor ring pigs and studying the behavior and spread of influenza viruses in these species.